Thermostability modification of β-mannanase from Aspergillus niger via flexibility modification engineering - Tan, Shundong; Tao, Xiumei; Zheng, Pu; Chen, Pengcheng; Yu, Xiaowei; Li, Ning; Gao, Tiecheng; Wu, Dan (Frontiers in Microbiology, 2023)
The enzyme β-mannanase is widely used in industrial applications. In this study, we heterologously expressed a mannanase (Anman) strain from Aspergillus niger CBS513.88 in Pichia pastoris and found that it had the highest activity at pH 3.0 and 72.5°C with a molecular weight of approximately 47 kDa. The wild-type mannanase Anman remains stable below 65°C but inactivates rapidly at 70°C. To further improve the thermostability of Anman, we screened multiple mutation sites using B-factor and Gibbs unfolding free energy change, and then combined with multiple sequence alignment and consensus mutation to generate five excellent single-point mutants, the thermostability of combined mutant mut5 (E15C/S65P/A84P/A195P/T298P) was 70% increased than wild type Amman at 70℃, and the melting temperature (Tm) and half-life (t1/2) values were increased by 2°C and 7.8 folds, respectively. Molecular dynamics simulation showed reduced flexibility and additional chemical bonds in the region near the mutation site. These results indicate that we obtained a mannanase mutant that is more suitable for industrial application, and also confirm that a combination of rational and semi-rational techniques is helpful for screening mutant sites.